Psychometric Properties of the ICF Core Set for Low Back Pain and Its Clinical Use - Derya ÖZTUNA,; Burcu YANIK,; Şehim KUTLAY,; Yeşim KURTAİŞ AYTÜR,; Atilla Halil ELHAN,; Alan TENNANT,; Ayşe Adile KÜÇÜKDEVECİ, (Archives of Rheumatology, 2011)
Objectives: In this study, we investigated the psychometric properties of the International Classification of Functioning, Disability and Health (ICF) core set for low back pain (LBP). Patients and methods: One-hundred outpatients with LBP (73 females, 27 males; mean age 55.3 years; range 24 to 84 years) were assessed by the ICF core set for LBP. The patients also completed the Roland-Morris disability questionnaire (RMDQ) and Short Form-36 (SF-36) questionnaire. The internal construct validity of the ICF core set for LBP was assessed by Rasch analysis and external construct validity by correlations with the RMDQ and SF-36 Health Survey version 1.0. Reliability was tested by internal consistency and person separation index. Results: After rescoring the disordered response categories and deletion of some items, “body functions and body structures” and “activities and participation” item sets satistifed Rasch model expectations with a mean item fit of 0.005 (SD 0.619) and −0.006 (SD 0.730), and person fit of −0.165 (SD 0.561) and −0.084 (SD 0.806) respectively. Both item sets were unidimensional and showed no differential item functioning. Their reliabilities were good with Cronbach's alpha coefficient and person separation index levels above 0.77. Although the mean functionality level of the patients was lower than the mean difficulty level of the items, the distribution of the difficulty level of the items overlapped with the distribution of the functionality level of the patients for both item sets. The presence of the expected level of correlations between both item sets and RMDQ and SF-36 has confirmed the external construct validity. “Environmental factors” did not meet the assumptions of the Rasch analysis. Conclusion: After some modifications, a 15-item “body functions and body structures” set and a 21-item “activities and participation” set from the ICF comprehensive core set were found to be reliable and valid to assess functioning in patients with LBP.